Effect of Horse-chestnut seed extract on matrix metalloproteinase-1 and-9 during diabetic wound healing - ŞEN, ALİ; ŞENER, AZİZE; AKSOY, HALİL; ŞEKERLER, TURGUT (WILEY, 2019)
The effects of aqueous-ethanol extract of Horse chestnut (HCE) on MMP-1 and MMP-9 expressions during cutaneous wound healing in diabetic rats were investigated in this study. The expressions of MMP-1 and MMP-9, wound closure, myeloperoxidase (MPO) activity, hydroxyproline, and malondialdehyde (MDA) levels in wound tissue were measured. Quercetin glucuronide in HCE was identified as main compound using a LC-MS/MS. The hydroxyproline level was significantly increased in the treated group versus control after the 3rd and 7th days (p < 0.05). The MDA level and MPO activity were significantly lower in the treatment group (p < 0.05). MMP-1 gene expression level in treated rats was increased in the 7th day while it was reduced in 14th day. MMP-9 gene expression level in treated rats was decreased in 7th, and 14th days compared to control (p < 0.05). These results show that HCE accelerated the cutaneous wound-healing process in diabetic rats via MMP-1 and MMP-9 regulation.
Keywords: diabetic wound; Horse chestnut seed extract; LC-MS/MS; matrix metalloproteinase-1; matrix metalloproteinase-9; wound healing; AESCULUS-HIPPOCASTANUM L.; PHENOLIC-COMPOUNDS; OXIDATIVE STRESS; LEAF TISSUES; ANTIOXIDANT; EXPRESSION; QUERCETIN; EFFICACY; INHIBITOR; AESCIN